The Relationship Between Age, Gender, Family Caregiver Burden on Family Coping in Hypertensive Patients with Stroke Comorbidity - Ika Nur Azizah; Sri Rahayu (Viva Medika, 2024)
Hypertension is a significant non-communicable disease, with a global prevalence of 29.4% in 2021. This research aims to explore the relationship of age, gender, and family caregiver burden on family coping skills in caring for hypertensive patients with stroke complications. Using a quantitative research design, we selected 76 caregivers at Dr. Moewardi Surakarta Hospital through purposive sampling. Data were collected by use of the Zarit Burden Interview (ZBI) and Family Crisis Oriented Personal Evaluation Scales (F-COPES) questionnaires. The findings show that there is no significant relationship between age and coping ability (p = 0.280). However, a significant association between gender and coping strategies was found, with 34.2% of males using adaptive coping compared to only 5.3% of females (p < 0.001). In addition, caregiver burden had a significant effect on coping ability, with 61.8% of caregivers who experienced heavy burden tending to use maladaptive coping. These findings emphasize the importance of social support and gender-tailored interventions to improve caregiver well-being and patient care